Low-temperature cold plasma promotes wound healing by inhibiting skin inflammation and improving skin microbiome - Zhou, Jie; Sun, Zengkun; Wang, Xiaoru; Wang, Shouguo; Jiang, Wen; Tang, Dongqi; Xia, Tao; Xiao, Fang (Frontiers in Bioengineering and Biotechnology, 2025)
Wound healing includes four consecutive and overlapping stages of hemostasis, inflammation, proliferation, and remodeling. Factors such as aging, infection, and chronic diseases can lead to chronic wounds and delayed healing. Low-temperature cold plasma (LTCP) is an emerging physical therapy for wound healing, characterized by its safety, environmental friendliness, and ease of operation. This study utilized a self-developed LTCP device to investigate its biological effects and mechanisms on wound healing in adult and elderly mice. Histopathological studies found that LTCP significantly accelerated the healing rate of skin wounds in mice, with particularly pronounced effects in elderly mice. LTCP can markedly inhibit the expression of pro-inflammatory cytokines (TNF-α, IL-6, IL-1β) and senescence-associated secretory phenotype factors (MMP-3, MMP-9), while significantly increasing the expression of tissue repair-related factors, such as VEGF, bFGF, TGF-β, COL-I, and α-SMA. It also regulated the expression of genes related to cell proliferation and migration (Aqp5, Spint1), inflammation response (Nlrp3, Icam1), and angiogenesis (Ptx3, Thbs1), promoting cell proliferation and inhibit apoptosis. Furthermore, LTCP treatment reduced the relative abundance of harmful bacteria such as Delftia, Stenotrophomonas, Enterococcus, and Enterobacter in skin wounds, while increasing the relative abundance of beneficial bacteria such as Muribaculaceae, Acinetobacter, Lachnospiraceae NK4A136_group, and un_f__Lachnospiraceae, thereby improving the microbial community structure of skin wounds. These research findings are of significant implications for understanding the mechanism of skin wound healing, as well as for the treatment and clinical applications of skin wounds, especially aging skin.